A comparison of new technology vehicle airborne emissions and energy usage. (1st January 2001) - Coffey, Robert A.; Sorenson, Spencer C.
This paper examines electric, hybrid electric and fuel cell electric vehicles. Comparisons have been made with the EURO I and EURO IV gasoline car, for the year 2005, on the basis of energy usage and airborne pollutants, generated both at the point of use and over the whole energy cycle. The study shows that on average, across EU15 countries, the electric vehicle will generate much reduced quantities of CO2, compared with the EURO IV gasoline car, but higher levels of NOx and SO2 . The gasoline hybrid electric vehicle and methanol fuel cell electric vehicle are anticipated to generate relatively low quantities of local pollutants, as well as, reduced NOx and SO2 emissions over the whole energy cycle. Benefits in terms of CO2 production are also indicated when compared with the EURO IV gasoline car.